Membangun Pendidikan Karakter Dalam Drama Gong “Ni Diah Tantri” di Live Streaming TVRI Bali Pada Tanggal 24 April 2021, 1 Mei 2021, dan 8 Mei 2021 - Ni Nyoman Suwiti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This paper uses a qualitative approach because it aims to describe the behavior of a person or a situation in a certain place in detail and in depth in the form of a narrative. Data collection techniques through external participation and documentation study which contains documents in the form of art works that were filmed In Key studies (in Satori and Komariah,2020:144-145) external participation is observations made via radio, television or reading in libraries. In today's technology there is no doubt that external participation is a fairly effective tool to help writers clarify and record events in gathering the required data. The data obtained were then analyzed by applying the semiotic theory. The character values will be later interpreted, contained in the gong drama